Marble Powder Blended Utilization Polyurethane as Soundproof Materials - Yusrizal MT; Muhammad Ali; Nuzuli Fitriadi; Irwansyah Syam; Balkhaya; Herdi Susanto (LPPM Politeknik Aceh Selatan, 2021)
As technology advances, the development of equipment used by humans is increasing and most of the equipment produces unwanted sounds that cause noise. To overcome this, an alternative material for soundproofing is needed which is relatively cheap and easily available in the community by using marble powder as a polyurethane mixture in soundproof panels. The purpose of this study was to determine the effect of the sound absorption coefficient value and to determine the relationship between the frequency of the sound source and the sound absorption coefficient of acoustic materials using marble powder mixed with polyurethane in different compositions. The sound absorption test in this study was carried out using a two-microphone impedance tube and has a frequency limit of 125 Hz - 4000 Hz, variations in the mass composition of marble and polyurethane powder 1: 1, 1: 2 and 1: 3 with a thickness of 5 cm, 3cm and 1 cm. Then the test results of the 1: 1 test specimen, the lowest sound absorption coefficient value was obtained 0.10 0.73 cm-1 at a thickness of 1 cm with a frequency of 4000 Hz and the highest was 0.73 cm-1 at a thickness of 5 cm with a frequency of 125 Hz, the test results 1: 2 test specimen, the lowest sound absorption coefficient value is 0.29 cm-1 at a thickness of 5 cm at a frequency of 4000 Hz and the highest is 0.67 cm-1 at a thickness of 5 cm at 250 Hz, then the test results of the test specimen are 1: 3 values The lowest sound absorption coefficient was 0.24 at a thickness of 1 cm at a frequency of 4000 Hz and the highest was 0.71 at a thickness of 5 cm at a frequency of 250 Hz. For the comparison of the sound absorption coefficient values ​​based on the composition and thickness, the lowest and highest sound absorption coefficient values ​​are found in 1: 1 specimens with a thickness of 1 cm and 5 cm with the best sound absorption coefficient values ​​on average at a frequency of 500 Hz, but in material 1:2 and 1:3 obtained the sound absorption coefficient values ​​are in between on the grounds that the thicker the material, the higher the sound absorption coefficient value. Thus it can be concluded that the polyurethane composite material mixed with marble powder can be used as a sound absorbing panel material, especially in a 1: 1 composition